Effectiveness of Neuromotor Task Training for Children with Developmental Coordination Disorder: A Pilot Study - M. M. Schoemaker; A. S. Niemeijer; K. Reynders; B. C. M. Smits-Engelsman (Neural Plasticity)
The aim of this pilot study was to evaluate the effectiveness of a Neuromotor Task Training (NTT), recently developed for the treatment of children with Developmental Coordination Disorder (DCD) by pediatric physical therapists in the Netherlands. NTT is a task-oriented treatment program based upon recent insights from motor control and motor learning research. Ten children with DCD (intervention group) were tested before and after 9 and 18 treatment sessions on the Movement ABC and a dysgraphia scale in order to measure the effectiveness of treatment on gross and fine motor skills in general and handwriting in particular. Five children (no-treatment control group) were tested twice with a time lag of nine weeks on the Movement ABC in order to measure spontaneous improvement. No improvement was measured for the children in the notreatment control group, whereas a significant improvement was found for children in the intervention group for both quality of handwriting and performance on the Movement ABC after 18 treatment sessions.